Propuesta de aplicación de buenas prácticas de manufactura en los procesos de higiene y manipulación de alimentos en el asadero “Rico Pollo” ubicado en el cantón Montalvo provincia de Los Ríos, Ecuador. Año 2024. - Alvarado Macias, Karla Fiorela (2024)
The main objective of this research project was the creation of a Good Manufacturing Practices Manual to improve higiene and food handling processes at the Rico Pollo roastery, located in the Montalvo cantón. This approach directly seeks to guarantee food safety for the establishment´s customers. The methodology used was based on a qualitative approach, with methodological background that includes the deductive method and extensive descriptive, exploratory reearch, both field and bibliographic. During the development of the Project, it was observed that the roastery was not adequately applying the necessary measures in food handling, which resulted in a lack of food higiene and por conservation. This was due, in part, to incorrect mana gement of solid waste, which generated contamination for producers and increased the risk of illness for consumers. It is important to highlight that the implementation of a Good Manufacturing Practices Manual in food hygiene and and handling processes is essential to guarantee food safety and producto quality. Therefore, it is strongly recommended that rigorous monitoring be established in the sanitation and control procedures for raw materials in the establishment.